The relationship of narcissism to professional satisfaction a field study on sport activity managers in Iraq - Sabri Mohammed Ali, Khansaa (International Journal of Psychosocial Rehabilitation, 2020)
The importance of research on the subject matter of narcissism because it is one of the recent topics that were dealt with in the library. The researcher also derives its importance from the nature of the types of managers, and there were no recent studies on a different topic with white satisfaction. The problem of searching for the characteristic of narcissism is to identify their relationship to professional satisfaction. Research aims are to identify the two measures of narcissism and professional satisfaction that were formed in the research sample. Identify differences in results between general managers in the two scales of narcissism and professional satisfaction. There are no statistically significant differences between the two measures of narcissism and occupational satisfaction among the research sample. There are no statistically significant differences between the general managers in the two measures of narcissism and occupational satisfaction. The researcher also used the descriptive approach in an intentional way to suit the nature of the research problem. The research sample was represented by managers of sports activity in Iraq except for the Kurdistan region, and their number was 20. After applying the standards, the researcher extracted the results, which were analyzed and discussed according to statistical means. The results are in the two scales of narcissism personality and professional satisfaction of the research sample. As for the researcher's recommendations, the topic of narcissism has not received sufficient attention in our society, as the researcher hopes that this study will be a scientific addition.